Africalolampra ehrmanni New Genus and Species, and the Male of Paraplecta Parva Princis (Blattaria: Blaberidae) - Louis M. Roth (Psyche: A Journal of Entomology)
A new cockroach genus and species, Africalolampra ehrmanni (Epilamprinae) from Kenya, and the previously unknown male of Paraplecta parva Shelford (Perisphaeriinae) from Uganda, are described.